2020
DOI: 10.1002/ejoc.202000553
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Reversible Dynamics of Pyrimidine Based Acylhydrazones

Abstract: We employed (Z)‐N'‐[phenyl(pyrimidin‐2‐yl)methylene]nicotinohydrazide (2) and (Z)‐4‐(dimethylamino)‐N'‐[phenyl(pyrimidin‐2‐yl)methylene]benzohydrazide (3) as cores of dynamic chemical systems whose different states are modulated, in a reversible fashion, through specific physical and chemical stimuli. The structure of the compounds was determined by Nuclear Magnetic Resonance (NMR) techniques (1D and 2D) and confirmed by single‐crystal X‐ray diffraction. By Variable temperature (VT) 1H NMR experiments and DFT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Hydrazones experience E/Z isomerism, similar to the imines ( C=N ), where the presence of an additional nitrogen atom decreases the double‐bond character of the π‐system and facilitates isomerization [59] . They can be either photochemically or thermally activated and are usually facilitated by polar solvents, acid/base catalysts, or by electron‐donating substituents [12,59–61] . The uncatalyzed isomerization around the C=N bond is known to proceed via two different mechanisms: rotation (via a polar transition state) and inversion (via a nonpolar transition state) (Scheme 8).…”
Section: Importance Of the N−h Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrazones experience E/Z isomerism, similar to the imines ( C=N ), where the presence of an additional nitrogen atom decreases the double‐bond character of the π‐system and facilitates isomerization [59] . They can be either photochemically or thermally activated and are usually facilitated by polar solvents, acid/base catalysts, or by electron‐donating substituents [12,59–61] . The uncatalyzed isomerization around the C=N bond is known to proceed via two different mechanisms: rotation (via a polar transition state) and inversion (via a nonpolar transition state) (Scheme 8).…”
Section: Importance Of the N−h Groupmentioning
confidence: 99%
“…[59] They can be either photochemically or thermally activated and are usually facilitated by polar solvents, acid/base catalysts, or by electron-donating substituents. [12,[59][60][61] The uncatalyzed isomerization around the C=N bond is known to proceed via two different mechanisms: rotation (via a polar transition state) and inversion (via a nonpolar transition state) (Scheme 8). [62][63][64] Beyond the details of how isomerization proceeds, the configurational dynamic is attractive because the interconversion between two states offers the possibility of the development of molecular switches used for diverse purposes.…”
Section: Configurational Dynamicsmentioning
confidence: 99%
“…[78] Chaur et al reported that an acylhydrazone 16 linked to aromatic pyrimidyl, pyridyl, and phenyl groups shows 1) thermally induced syn-anti conformational isomerism, 2) E-Z photoisomerization about the C=N bond, and 3) deprotonation-driven E-Z configurational change (Figure 15). [79] The Z-anti form (antiperiplanar conformation of the NH-CO bond) of 16 was detected by X-ray crystallographic analysis. However, NMR spectroscopic analysis indicated that Z-syn-16 predominates in solution at 298 K and that conformational switching to the Z-anti form occurs at lower temperature.…”
Section: Molecular Switches and Motors Orthogonally Activated By Lighmentioning
confidence: 99%
“…Light-, heat-, and pH-driven conformational/configurational switching of acylhydrazone 16. [79] merocyanine (MC) form, is another class of multimodal molecular switches. [80] Switching is triggered by light and other stimuli, such as heat, solvent exchange, metal ions, redox potential, pH change, and mechanical force, [42,81] and two distinct modes of structural change (ring opening/closing and E-Z isomerization around the central double bond in the MC form) can be controlled independently.…”
Section: Molecular Switches and Motors Orthogonally Activated By Lighmentioning
confidence: 99%